Hysterotomy for Management of Dystocia due to Prepartum Vagino-Cervical Prolapse Coupled with Vaginal Tear in a Jersey Crossbred Cow - Sarath, Thulasiraman; Rangasamy, Seerangan; Arunmozhi, Narayanasamy; Kumar, Raju Suresh; Pugazharasi, Chidambaram (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Vagino-cervical prolapse is a common reproductive disorder of ruminants, usually seen in pluriparous cows in late gestation  and occasionally after parturition (Noakes et al., 2019). It is mainly  seen in ruminants, rare in other species, and usually involves  protrusion of the floor, the lateral walls, and a portion of the roof  of the vagina through the vulva with the cervix and uterus moving  caudally (Roberts, 2004). Predisposing factors include hereditary  factors in some cattle breeds, increased intra-abdominal pressure,  intra-abdominal fat or rum n distention, softening of the pelvic  ligaments, bacterial or fungal infections, hormonal imbalance,  hypocalcemia, mineral deficiency, and feed containing phyto estrogens like clover, soybean meal, etc. (Roberts, 2004; Miesner  and Anderson, 2008). Highconcentration of estrogen secreted by  the placenta in the last trimester of pregnancy causes relaxation of  the vulva, vulvar sphincter muscles, pelvic ligaments, and adjacent  structures, leading to vagino-cervical prolapse in cows (Roberts,  2004; Wolfe, 2009). A combination of increased estrogen with  decreased progesterone and production of relaxin, especially in  the last two weeks of gestation, may cause relaxation of the pelvic  ligaments and surrounding soft tissues (Henricks et al., 2011). The  present paper reports a rare case of dystocia due to prepartum  vagino-cervical prolapse coupled with a vaginal tear in a Jersey  crossbred cow and its successful delivery through hysterotomy.
Keywords: Dystocia; Vagino-cervical prolapse; ruminants